Project-Based Learning Model Assisted by Audio Visual Media Improves Description Writing Skills of Fifth Grade Elementary School Students - Ni Putu Clara Handayani; Maria Goreti Rini Kristiantari (Universitas Pendidikan Ganesha, 2023)
Students' skills in writing descriptions still need to improve. The lack of application of innovative and varied learning models causes it. This study aims to analyze the effect of the PjBL model assisted by audio-visual media on the descriptive writing skills of fifth-grade elementary school students. This type of research is quasi-experimental with a non-equivalent control group design. The population in this study were all fifth-grade students, totaling 310 students. The research sample was determined by cluster random sampling technique with a total of 32 students and fifth-grade students. The method and instrument used in this research was a test of Indonesian writing skills. Research data were analyzed using descriptive analysis techniques and inferential statistical analysis techniques. The result of the analysis is that the PjBL model assisted by audio-visual media affects the description writing skills of fifth-grade elementary school students. It was concluded that the PjBL model, assisted by audio-visual media, improved the descriptive writing skills of fifth-grade elementary school students. The implication of this research is using the PjBL model assisted by audio-visual media to help students learn so that it is suitable for learning, especially in Indonesian language content.